DESIGN OF QUEUING SYSTEM USING PRIORITY QUEUE ALGORITHM AND MULTI CHANNEL MULTI PHASE METHOD AT WEBSITE-BASED PATIENT REGISTRATION SECTION (CASE STUDY OF DONGGALA HEALTH CENTER) - Anita, Ayu; Ardiansyah, Rizka; Lapatta, Nouval Trezandy; Angreni, Dwi Shinta; Laila, Rahmah (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This research was conducted to regulate the queuing process which is often longer than the service standards set in the Decree of the Minister of Health Number 129 / Menkes / SK / II / 2008 stipulates that the waiting time for outpatients is equal to 60 minutes or less than 60 minutes, This study aims to design and build a website-based electronic queuing system at Puskesmas Donggala using the Priority Queue algorithm and the Multi Channel Multi Phase method. This system is designed to improve the efficiency of patient registration by reducing waiting time and providing priority for patients with emergency conditions. The research method includes data collection through observation and interviews, as well as system testing through simulation. The results show that the proposed system can reduce waiting time and increase patient satisfaction. The implementation of this system is expected to provide an effective solution to queuing problems in health facilities.